Capacity strengthening strategy through capacity needs assessment for Country Level Strategic Analysis and Knowledge Support System (SAKSS): Uganda - Bashaasha, Bernard (International Food Policy Research Institute, 2014)
In an effort to accelerate growth and eliminate hunger and poverty, Uganda signed a Comprehensive Africa Agriculture Development Programme Compact in 2010, thereby agreeing to commit 10 percent of its annual budget toward agriculture and to work toward increasing the sector’s growth by 6 percent annually. To support these objectives, stakeholders need adequate capacities to develop policies and address the country’s food and agriculture needs. The purpose of this 2012 capacity needs assessment is to identify gaps in the agricultural policymaking process caused by limited or nonexistent capacities and develop an action plan to close these gaps.